THE ASSOCIATION OF AGE AND PARITY WITH THE INCIDENCE OF OVARIAN CANCER IN WOMEN OF CHILDBEARING AGE AT RSUP H. ADAM MALIK MEDAN YEAR 2023 - Lahagu, Median Jelita; Manururng, Herna Rinayanti; Sari, Febriana; Damanik, Lisa Putri Utami (Journal of Public Health Science, 2024)
One of the reproductive health issues of concern is cancer. Cancer is one of the causes of death in the world. Ovarian cancer is known as the sillent killer because in the early stages of the disease does not show early symptoms. Ovarian cancer is a deadly malignant disease in gynaecology, and one of the most malignant causes of death in the world. Maternal age and parity are several types of factors that can affect the incidence of ovarian cancer. This study aims to determine the relationship between maternal age and parity with the incidence of ovarian cancer at H. Adam Malik Medan Hospital in 2023. Methods: This study is a Cross Sectional study. The sample in this study was 79 women of childbearing age in the H. Adam Malik Hospital room with a ratio of 2: 1, namely 79 case groups (WUS with Ovarian Cancer) taken using simple random technique. Data analysis technique using Chi-Square Results: Based on the frequency of mothers whose age is at risk of ovarian ca as many as 27 respondents (52.9%), then in mothers with age who are not at risk as many as 9 respondents (32.1%). Then in mothers with no ovarian ca parity at risk as many as 15 respondents (41.1%) and in mothers with parity who are not at risk as many as 19 respondents (67.9%). The results of the Chi Square test obtained a p value of 0.124, this indicates that there is no significant relationship with parity on the incidence of ovarian ca at the Adam Malik Hajj Hospital in 2023. Conclusion: Based on the results of the study, it shows that mothers with at-risk age (>40 years) and mothers with at-risk parity (≤ 0 and >2) are more prone to ovarian cancer. Keywords: Age, Parity, Ovarian Cancer